Simuliidae da Amazônia VI. Descrição do Simulium meruoca sp. n. (Diptera, Nematocera) - Mello, José A. Nunes de; Almeida, Flávio Barbosa de; Dellome Filho, Júlio (Acta Amazonica, 1973)
The authors describe a new species of Diptera-Simuliidae; Simulium meruoca. This species was collected on the BR-401 road, between the localities of Boa Vista and Bonfim. in the Federal Territory of Roraima.